Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Assets Pada PT. Wismilak Inti Makmur Tbk Periode 2014-2023 - Melisa Bestiana; Yulian Bayu Ganar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The aim of this research is to find out how the financial performance of PT. Wismilak Inti Makmur Tbk for the 2014-2023 period uses the financial reports of PT. Wismilak Inti Makmur Tbk for the 2014-2023 period. This research method uses quantitative methods, the data used is secondary data obtained from the website https://www.wismilak.com/. Data analysis techniques use descriptive statistical tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, coefficient of determination analysis, T test, F test using SPSS Version 26 software. The results of this research show partial Current Ratio ( CR) has a negative effect on Return On Assets (ROA) at PT Wismilak Inti Makmur Tbk for the 2014-2023 period. based on partial results, the Debt to Equity Ratio (DER) has no significant effect on Return On Assets at PT. Wismilak Inti Makmur Tbk for the period 2014-2023. Simultaneously, Current Ratio (CR) and Debt To Equity Ratio (DER) have a significant effect on Return On Assets (ROA) at PT Wismilak Inti Makmur Tbk for the 2014-2023 period